CASH RATIO SEBAGAI SALAH SATU FAKTOR YANG MEMPENGARUHI CASH DIVIDENDS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2013 - Tri Rinawati; Aprih Santoso (STIE Pelita Nusantara Semarang, 2016)
This study aims to examine the factors that affect Cash Dividends. Generally, investors in receipt of dividends over the company wants to make a payment in cash, this is due to the dividend payment in cash would reduce the risks of uncertainty in carrying out investment activities in a company.The type of data in this research is secondary data is data obtained from third parties. Secondary data used in this study comes from external data obtained from the Indonesia Stock Exchange (BEI).This study uses linear regression to examine the effect of Earning Per Share, Cash Ratio, Operating Cash Flow to Cash Dividends. The sample used in this research is manufacturing companies listed in Indonesia Stock Exchange in 2010 - 2013. The total sample is 11 companies were determined by purposive sampling method.The results of this study indicate that the Earning Per Share, Cash Ratio, Operating Cash Flow effect on Cash Dividends. These results are consistent with research conducted by Darvil (2012) also Ramli and Mohammed Ridha Mohammed Arfan (2011) that the variable operating cash flow and cash ratio effect on cash dividends